2013
DOI: 10.1371/journal.pone.0064263
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Dietary Restriction Alters Offspring’s Sleep Homeostasis

Abstract: Nutritional state in the gestation period influences fetal growth and development. We hypothesized that undernutrition during gestation would affect offspring sleep architecture and/or homeostasis. Pregnant female mice were assigned to either control (fed ad libitum; AD) or 50% dietary restriction (DR) groups from gestation day 12 to parturition. After parturition, dams were fed AD chow. After weaning, the pups were also fed AD into adulthood. At adulthood (aged 8–9 weeks), we carried out sleep recordings. Alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 35 publications
(45 reference statements)
0
6
0
Order By: Relevance
“…CPT1C, as a functional enzyme in the outer mitochondrial membrane, is linked to lipid metabolism and cellular energy supply [16,17]. Besides the regulation of fatty acid oxidation, CPT1C also plays an important role in other physiological and pathological processes [18][19][20][21]. The current study revealed that CPT1C depletion is sufficient to trigger a senescence phenotype in other cancer cell lines.…”
Section: Discussionmentioning
confidence: 56%
“…CPT1C, as a functional enzyme in the outer mitochondrial membrane, is linked to lipid metabolism and cellular energy supply [16,17]. Besides the regulation of fatty acid oxidation, CPT1C also plays an important role in other physiological and pathological processes [18][19][20][21]. The current study revealed that CPT1C depletion is sufficient to trigger a senescence phenotype in other cancer cell lines.…”
Section: Discussionmentioning
confidence: 56%
“…CPT1C, an enzyme located in the outer mitochondrial membrane [32], is involved in lipid metabolism, cellular energy supply [33][34][35] and other physiological or pathological processes [36][37][38][39]. The knockdown of CPT1C inhibited the tumorigenesis of PANC-1 cells in vivo [2,33] and further suppressed xenograft tumor growth in situ [2], suggesting that CPT1C represents a therapeutic target for cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence that shows that maternal diets can affect the behavior of the offspring. One study showed that sleep homeostasis was affected by the maternal diet (17). Prenatal calorie restriction has been shown to have a wide range of effects on progeny.…”
Section: Neonatology Todaytwwwneonatologytodaynettseptember 2021mentioning
confidence: 99%